Short-Term High-Fat Diet (HFD) Induced Anxiety-Like Behaviors and Cognitive Impairment Are Improved with Treatment by Glyburide - Gainey, Stephen J.; Kwakwa, Kristin A.; Bray, Julie K.; Pillote, Melissa M.; Tir, Vincent L.; Towers, Albert E.; Freund, Gregory G. (Frontiers in Behavioral Neuroscience, 2016)
Obesity-associated comorbidities such as cognitive impairment and anxiety are an increasing public health burden that has gained prevalence in children. To better understand the impact of childhood obesity on brain function, mice were fed a high-fat diet (HFD) from weaning for 1, 3 or 6 wks. When compared to low-fat diet (LFD)-fed mice (LFD-mice), HFD-fed mice (HFD-mice) had impaired novel object recognition (NOR) after 1 wk. After 3 wks, HFD-mice had impaired NOR and object location recognition (OLR). Additionally, these mice displayed anxiety-like behavior by measure of both the open-field and elevated zero maze testing. At 6 wks, HFD-mice were comparable to LFD-mice in NOR, open-field and elevated zero maze performance but remained impaired during OLR testing. Glyburide, a second generation sulfonylurea for the treatment of type 2 diabetes, was chosen as a countermeasure based on previous data showing its potential as an anxiolytic. Interestingly, a single dose of glyburide corrected deficiencies in NOR and mitigated anxiety-like behaviors in mice fed HFD-diet for 3-wks. Taken together these results indicate that a HFD negatively impacts a subset of hippocampal-independent behaviors relatively rapidly, but that such behaviors normalize with age. In contrast, impairment of hippocampal-sensitive memory takes longer to develop but persists. Since single-dose glyburide restores brain function in 3-wk-old HFD-mice, drugs that block ATP-sensitive K+ (KATP) channels may be of clinical relevance in the treatment of obesity-associated childhood cognitive and psychopathologies.